2000
DOI: 10.1007/s002640000158
|View full text |Cite
|
Sign up to set email alerts
|

Limb salvage for proximal tibial tumours using a modular prosthesis

Abstract: We report early results after the resection of proximal tibial tumours followed by reconstruction using a modular prosthesis. The indication for wide resection was a malignant tumour in 13 patients, and a neglected giant cell tumour in 2. There were no mechanical failures during an average follow-up of 3.5 years. However, there were 5 peroneal nerve palsies, 1 complete sciatic nerve palsy, 1 vascular injury leading to an above knee amputation, and 2 deep prosthetic infections. There were 2 superficial skin nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Nevertheless, it has the advantage of allowing direct suture from host to allograft, minimising bone resection and preserving the articular surface of the distal femur and patella. Better final functional results were found compared with other methods [5,7,14].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, it has the advantage of allowing direct suture from host to allograft, minimising bone resection and preserving the articular surface of the distal femur and patella. Better final functional results were found compared with other methods [5,7,14].…”
Section: Introductionmentioning
confidence: 83%
“…These limitations may be attributed to difficulties in the reconstruction of the extensor mechanism [3,5,15]. A procedure used to overcome this problem is the medial gastrocnemius transposition to the residual patellar tendon [3,8,14]. In the osteochondral allograft surgical procedure, a higher incidence of infection, fractures, and loss of fixation is reported [5,12,17,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…Gait and stride length are, however, not significantly different between endoprosthetic replacement and above-knee amputation using an external prosthesis [26]. Endoprosthetic replacement is also associated with several possible complications like failure of primary wound healing, flap necrosis, secondary infection, aseptic loosening, fracture and breakage [1,13,15,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern chemotherapy the prognosis for malignant tumors has improved greatly and encouraged surgeons to consider limb salvage surgery in most cases [1]. The site of tumor is an important factor, however, as many studies have shown poor results in the treatment of proximal tibial tumors compared to distal femoral tumors [7,10,13]. The trend, therefore, may be shifting towards the use of prosthesis in limb salvage, particularly for distal femoral tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our preferred option following resection of the tumor is the use of a modular prosthesis, i.e., standard-sized components with varying lengths according to the amount of bone resected. This procedure has produced consistently better results for distal femoral tumors than for proximal tibial tumors for several reasons [7,10,13]. The prosthesis can be used either with or without cement [3,9,11], and results have been almost the same in both cases at midterm follow-up.…”
Section: Introductionmentioning
confidence: 93%